Measuring the Economic Impact of Halal Tourism in Strengthening Sustainable and Environmentally Friendly Destinations - Ade Elza Surachman; Dessy Kumala Dewi; Tolibova Aziza Tulkin kizi (Green Economics: International Journal of Islamic and Economic Education, 2024)
Halal tourism has emerged as a significant niche within the global tourism industry, offering a unique opportunity to integrate religious values with sustainable tourism practices. This study explores the economic, cultural, and environmental impacts of halal tourism, focusing on its role in fostering local economic growth, preserving cultural heritage, and promoting environmental sustainability. The research highlights key findings that show halal tourism not only drives economic growth by creating income opportunities and supporting small and medium enterprises (SMEs) but also ensures that tourism activities align with eco-friendly practices. The study emphasizes that halal tourism has the potential to integrate local wisdom and community engagement, which strengthens cultural preservation and promotes social cohesion within tourism destinations. Furthermore, halal tourism initiatives frequently incorporate sustainable tourism practices, such as responsible resource use and the conservation of natural ecosystems, thereby contributing to the broader goals of sustainable tourism development. The study compares halal tourism with traditional mass tourism, noting that halal tourism offers a more inclusive, culturally sensitive, and environmentally responsible model. It also examines the challenges faced by halal tourism, including the lack of standardized halal certification and infrastructure deficiencies, which hinder its growth in some regions. Despite these challenges, the research identifies opportunities for innovation, particularly in the use of technology to enhance certification systems and improve environmental sustainability. The paper concludes with policy recommendations for integrating halal tourism into sustainable tourism strategies, suggesting the need for coordinated frameworks that promote both halal compliance and environmental stewardship. Finally, future research should focus on the impacts of halal tourism in diverse geographic and cultural contexts, exploring its potential for fostering sustainable tourism practices worldwide.